Virtual Museum and Tour – the Added Value of a Web Site - Gontar, Beata (Management and Administration Journal, 2023)
Digital technology expands the possibilities for presentation of museum collections. That is why the museums are interested in the digitalizing their collections. It also makes the information content accessible to a wider range of visitors. New technologies, like augmented reality or podcasts, are used on museums’ web sites, and possibility of interesting new visitors is so important that a lot of museums invest in ICT projects and create virtual museums to present their collections online and to make their web site more interesting and attractive for new users.